Analisis Tindak Tutur Ilokusi dalam Film Komang Karya Naya Anindita - Leylil Nikmatur Rofiah; Farida Yufarlina Rosita; Berlian Pancarrani (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Film serves not only as entertainment but also as a medium for conveying messages through verbal interactions between characters. In pragmatics, illocutionary acts are central to understanding a speaker’s intention within a given context. This study aims to describe and analyze the types and functions of illocutionary speech acts in the Indonesian film Komang (2025) by Naya Anindita, which portrays a love story across religious and cultural boundaries. Using a descriptive qualitative approach, data were collected through observation and transcription of dialogue from the film. The analysis is based on Searle’s classification of illocutionary acts: representatives, directives, expressives, commissives, and declaratives. The findings reveal that all five types appear in the film, each playing a role in shaping interpersonal dynamics, emotional tension, and cultural values. Directive and expressive acts are the most dominant, reflecting intense emotional exchanges and social interactions. Commissive and declarative acts highlight commitment and authority, contributing to the narrative progression and cultural identity negotiation. The study concludes that illocutionary acts in films can represent social conflicts and cultural expressions, and recommends further research on other films with varied genres and contexts. The integration of multimodal elements is also suggested to enrich the analysis of meaning in audiovisual texts.